Protocol: Systematic Literature Review on coordination mechanisms for the mathematical programming models in production planning with decentralized decision making - Gregorio Rius-Sorolla; Julien Maheut; Sofía Estelles-Miguel; José Pedro Garcia-Sabater (WPOM : Working Papers on Operations Management)
The article presents the research protocol for a systematic literature review on the coordination mechanisms in the mathematical programming for decentralized decision making on the planning and scheduling, intra or inter companies from 2006 to 2016.